Analisis Kegagalan Rantai Timing Sepeda Motor Bebek Akibat Beban Tarik dengan Metode Tensile Test - Bhagaskara Teguh Samudra; Ade Irwan; Din Aswan Ritonga (Blend Sains Jurnal Teknik, 2023)
The timing chain is one of the components that play a major role in determining how the engine works by receiving rotation from the crankshaft. This rotation is useful for moving the camshaft which is located in the cylinder head. when the timing chain is loose it often gives an unexpected sound response that can cause the timing chain to quickly stretch. the timing chain will quickly stretch on a motorcycle that rarely gets new and fresh engine oil intake. lack of maintenance on engine oil will have an impact on many things. In addition to the timing chain which is easily loosened due to the lack of a lubricant formula in the engine oil, the research begins with finding and studying various supporting theories related to the strength and elongation of the timing chain. the method used in this research is the tensile test method using the UTM machine. universal testing machine. Material testing machine with a length of 26.5 mm. The research results have 5 specimens for the first specimen on the timing chain having a tensile stress with a value of 2,00 Mpa, a tensile strain with a value of 1,07 and a modulus of elasticity with a value of 1,86 Mpa. the second specimen on the timing chain has a tensile stress with a value of 1.4 Mpa, a tensile strain with a value of 1.07 and a modulus of elasticity with a value of 1.33 Mpa. The third specimen in the timing chain has a tensile stress with a value of 1.79 Mpa, a tensile strain with a value of 1.07 and a modulus of elasticity with a value of 1.67 Mpa. the fourth specimen in the timing chain has a tensile stress with a value of 1.96 Mpa, a tensile strain with a value of 1.15 and a modulus of elasticity with a value of 1.70 Mpa. the fifth specimen in the timing chain has a tensile stress with a value of 5.79 Mpa, a tensile strain with a value of 1. and a modulus of elasticity with a value of 5.79 Mpa.